Broiler Performance upon Dietary Substitution of Cocoa Husks for Maize - Teguia, A.; Endeley, H.N.L.; Beynen, A.C. (International Journal of Poultry Science, 2004)
Anack 180 broiler chickens, aged 7 weeks, were used in an experiment to determine the effect of replacement of maize by cocoa husks in a grower-finisher ration. Cocoa husks were substituted for the maize component in the ration (65 g maize/100 g of diet) at levels of either 0, 10, 20 or 30% of the maize. The birds fed the diet with the 10% substitution level showed significantly faster growth than the control animals whose growth rates were not significantly different from the birds fed the diet with 20% maize replacement. When compared with the control birds, low body weight and poor efficiency of feed utilization were observed for the birds fed the diet with 30% maize replacement. Cocoa husks are less expensive than maize, but cost analysis indicated that the feed cost per kg of live broiler was increased after incorporation of cocoa husks into the diet. It is concluded that cocoa husk might be used as an ingredient for poultry grower finisher diets, but various questions need to be addressed prior to practical application.